2023
DOI: 10.1108/ijbm-04-2022-0157
|View full text |Cite
|
Sign up to set email alerts
|

High-involvement work practices, work engagement and their effects on bank employees' turnover intentions: the moderating role of functional competence

Abstract: PurposeThis study aims to propose and examine a research model where work engagement mediates the impacts of high-involvement work practices (HIWPs) on bank employees' turnover intentions. Specifically, the paper assesses: (a) the effects of empowerment, information sharing, rewards and training on work engagement and turnover intention, (b) work engagement as a mediator of the effects of these HIWPs on turnover intention (c) and functional competence as a moderator of the effects of these HIWPs on work engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Studies found that a compensation system can be used as a key strategy for improving employee commitment and retention (Horwitz et al ., 2003; Mahmood et al ., 2019). Researchers have shown that rewards and recognition are crucial factors influencing affective commitment, work engagement and turnover intention (Islam et al. , 2023a, b).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies found that a compensation system can be used as a key strategy for improving employee commitment and retention (Horwitz et al ., 2003; Mahmood et al ., 2019). Researchers have shown that rewards and recognition are crucial factors influencing affective commitment, work engagement and turnover intention (Islam et al. , 2023a, b).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In turn, this tarnishes FLEs' service encounters (Hur and Kim, 2020;Kamran-Disfani et al, 2022), thereby leading to service sabotage (Kao et al, 2014;Kashif and Zarkada, 2015;Yue et al, 2021) and hindering of their performance (Walker et al, 2014;Yavas et al, 2013). Ultimately, turnover rates amongst FLEs increase, resulting in higher recruitment costs (Islam et al, 2023;Han et al, 2016). Nonetheless, examining customer incivility and its effects reveals a lack of coverage in the existing literature, as reported in a recent systematic review (Chaudhuri et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…, 2013). Ultimately, turnover rates amongst FLEs increase, resulting in higher recruitment costs (Islam et al. , 2023; Han et al.…”
Section: Introductionmentioning
confidence: 99%
“…There are so many gaps pointed out by the researchers over time. Firstly, studies often focus on either positive or negative impacts, overlooking two contrasting perspectives: the optimistic view (mutual gains) and the pessimistic view (conflicting outcomes; Islam et al, 2023 ). Studies on positive relationships between HIWPs and employee outcomes are common, suggesting that employers and employees benefit from HIWPs, leading to positive employee behavior and improved organizational performance ( Dongsen, 2023 ).…”
Section: Introductionmentioning
confidence: 99%